ANALISIS PENGARUH BEBAN PAJAK, PROFITABILITAS, DAN NILAI TUKAR MATA UANG TERHADAP TRANSFER PRICING PADA PERUSAHAAN SEKTOR CONSUMER NON CYILICALS SUB SEKTOR FOOD & BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2024 - Rani Titi Rohmani; Diana Airawaty (ITB AAS Indonesia Surakarta, 2026)
This study was conducted to analyze and analyze the effect of tax burden, profitability, and currency exchange rates on transfer pricing in consumer non-chemical companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The study population consisted of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. The data analysis technique used SPSS. The SPSS output shows that tax burden has no effect on transfer pricing. This result indicates that H1 is rejected. Profitability has a negative effect on transfer pricing. This result indicates that H2 is accepted. Currency exchange rates have a positive effect on transfer pricing. This result indicates that H3 is accepted.